Modification of the abductor digiti minimi muscle flap for soft tissue coverage of the diabetic foot. (1st July 2020) - Ramanujam, Crystal L; Suto, Alan C; Zgonis, Thomas
Abstract : The local intrinsic abductor digiti minimi muscle flap is ideal for lateral, plantar lateral traumatic or diabetic foot wounds following adequate surgical debridement to eradicate any soft tissue and/or osseous infection. Although the indications and surgical technique have been well-described in the literature, the authors present a unique modification of tunnelling the harvested muscle flap directly from the donor site to the plantar recipient foot wound by maintaining the intact overlying skin island at the surface of the fifth metatarsal base. This modification allows preservation of the patient's skin integrity in this area, thereby minimising potential morbidity at the major pedicle site. After the harvested muscle is tunnelled through the intact skin island, an adjacent local random flap mobilisation, autogenous or allogeneic skin graft can then be used for coverage over the muscle inset if primary wound closure is not feasible. Simultaneous soft tissue or osseous surgical procedures and/or surgical offloading with external fixation at the time of index surgery may be necessary to achieve optimal outcomes. The authors present a modified surgical technique for the abductor digiti minimi muscle flap that can be performed in the surgical reconstruction of a soft tissue wound in patients with diabetic Charcot neuroarthropathy.